Green Innovation: The Case Study of Innovative Portuguese SMEs - Matos, F.; Dias, C. C.; Marques, C. (7 th International Conference on Industry of the Future and Smart Manufacturing, 2025)
This study examined the approach to green innovation strategies among Portugal’s most innovative Small and Mediumsized Enterprises (SMEs). This study adopts a research method based on case studies, in which the unit of analysis is the company, thus allowing an in-depth analysis of green innovation within SMEs. In addition, it was carried out an analysis of websites and official documents, such as sustainability reports, financial reports, and magazines, which allowed for the capture perspectives not mentioned in the interviews and the exploration some further topics. Furthermore, the study reveals that companies are adopting resource conservation and waste management to reduce environmental impact, where the successful implementation of green innovations hinges upon establishing an environmental orientation within the organization and fostering a culture of innovation, supported by consultancy services, fiscal incentives, external financing, internal R&D, and partnerships which are identified as accelerators of green innovation. Barriers such as investment costs, societal attitudes, the global landscape, bureaucratic hurdles, and legislation pose challenges to the implementation. Nonetheless, although providing valuable insights, the research paper suffers from limitations, such as the small sample size of 13 SMEs may not be representative of the broader population, and the qualitative methodology, while helpful for understanding perspectives, lacks the generalizability of quantitative studies. Finally, the paper could explore the identified barriers to green innovation in more depth, providing specific examples and analyzing their relative importance.